The influence of Working Capital Turnover, Debt to Asset Ratio, and Fixed Asset Turnover on Return on Asset in F & B Company Listed on the IDX in 2019-2023 - Musmar, Ismail Mahara; Siregar, Muhammad Yamin (Cattleya Darmaya Fortuna, 2025)
This study examines the impact of Working Capital Turnover (WCT), Debt to Asset Ratio (DAR), and Fixed Asset Turnover (FATO) on Return on Assets (ROA) in F&B companies listed on the IDX (2019-2023). Using panel data and a quantitative approach, the research employs panel data regression, classical assumption tests, t-tests, F-tests, and the coefficient of determination. Results show that WCT and FATO have a positive but insignificant effect on ROA, while DAR has a negative and significant effect. Simultaneously, all three variables have no significant effect on ROA.